2006
DOI: 10.2527/2006.842387x
|View full text |Cite
|
Sign up to set email alerts
|

Site and extent of digestion, duodenal flow, and intestinal disappearance of total and esterified fatty acids in sheep fed a high-concentrate diet supplemented with high-linoleate safflower oil

Abstract: Our objective was to determine duodenal and ileal flows of total and esterified fatty acids and to determine ruminal fermentation characteristics and site and extent of nutrient digestion in sheep fed an 80% concentrate diet supplemented with high-linoleate (77%) safflower oil at 0, 3, 6, and 9% of DM. Oil was infused intraruminally along with an isonitrogenous basal diet (fed at 2% of BW) that contained bromegrass hay, cracked corn, corn gluten meal, urea, and limestone. Four crossbred wethers (BW = 44.3 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 26 publications
6
27
0
3
Order By: Relevance
“…Although lipolysis is a prerequisite of rumen BH, in vivo studies reporting dietary and digesta EFA and NEFA fractions are scarce [15][16][17]. Omasal or abomasal sampling offers the greatest opportunity for the correct assessment of rumen lipolysis, without the risk of intestinal hydrolysis.…”
Section: Rumen Lipolysismentioning
confidence: 99%
“…Although lipolysis is a prerequisite of rumen BH, in vivo studies reporting dietary and digesta EFA and NEFA fractions are scarce [15][16][17]. Omasal or abomasal sampling offers the greatest opportunity for the correct assessment of rumen lipolysis, without the risk of intestinal hydrolysis.…”
Section: Rumen Lipolysismentioning
confidence: 99%
“…Plascencia et al (2003) explained that the low intestinal digestibility of fat is due to extensive ruminal biohydrogenation of fatty acids. Additionally, Atkinson et al (2006) indicated that feeding highconcentrate diets can result in decreased ruminal biohydrogenation, which can lead to greater unsaturated fatty acid concentrations in tissues. This, coupled with lower fat intakes may explain why cattle fed the CON and CON + OIL diets had greater total fat digestibility than cattle fed the COMP and COMP + OIL diets.…”
Section: Methodsmentioning
confidence: 99%
“…Results of CP and NDF digestibilites are consistent with the findings of Manso et al (2006) who fed growing lambs diets containing calcium salts (MAGNAPAC) similar to the fat source used in the present study. Similarly, Atkinson et al (2006) observed no differences on OM, CP, and NDF digestibilities when crossbred whether lambs were fed high concentrate diets supplemented with high-linoleate safflower oil at levels of 0%, 3%, 6%, and 9%. However, our results for ADF digestibility disagreed with previous studies that reported that inclusion of fat decreased ADF digestibility (Reddy et al 2003;Appeddu et al 2004;Manso et al 2006).…”
Section: Resultsmentioning
confidence: 74%